2010
DOI: 10.1177/0145482x1010400706
|View full text |Cite
|
Sign up to set email alerts
|

The Social Lives of Canadian Youths with Visual Impairments

Abstract: This survey of the social and leisure experiences of Canadian youths with visual impairments found that, in general, youths with low vision experienced more social challenges than did their peers who were blind. Levels of social support were not found to differ on the basis of level of vision, sex, or age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 9 publications
(12 reference statements)
3
40
0
9
Order By: Relevance
“…Just as previous studies (5,(7)(8)(9) have shown, young people with visual impairment were in this study too found to have few friends and often to consider themselves as lonely. The results also support a Canadian study on the social and leisure experiences of young people with visual impairments, which found that, in general, young people with low vision experienced more social challenges than did their peers who were blind (23). This study found that young people with mild visual impairment tried to manage without assistive devices and hence underperformed at school or in social situations.…”
Section: Discussionsupporting
confidence: 82%
“…Just as previous studies (5,(7)(8)(9) have shown, young people with visual impairment were in this study too found to have few friends and often to consider themselves as lonely. The results also support a Canadian study on the social and leisure experiences of young people with visual impairments, which found that, in general, young people with low vision experienced more social challenges than did their peers who were blind (23). This study found that young people with mild visual impairment tried to manage without assistive devices and hence underperformed at school or in social situations.…”
Section: Discussionsupporting
confidence: 82%
“…Kef et al ; Kroksmark & Nordell ; Kef & Bos ; Sacks & Wolffe ; Gold et al. ), this seems unlikely. A possible explanation for the low percentage of rehabilitation needs in these chapters is that young adults may not feel comfortable sharing issues about relationships in their encounter with the intaker.…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies found that adolescents with visual impairments experienced difficulties in this regard, threatening psychosocial development and the quality and maintenance of such relationships (Kroksmark & Nordell ; Kef ; Kef & Deković ; Kef & Bos ; Sacks & Wolffe ; Gold et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, matches that comprise mentors and mentees who both have a VI face added challenges that are associated with the VI itself. Specifically, having VI can result in restricted mobility (Berger, ) and has been found to be related to problems with social competence (Gold et al., ; Kef & Bos, ). If one or more of these practical or interpersonal challenges are present in both members of the match, then these challenges may mitigate against the potential positive effect associated with disability similarity and potential benefits of having had similar life experiences related to VI.…”
Section: Discussionmentioning
confidence: 99%